2015
DOI: 10.1186/s40712-015-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler addition on solidification behaviour and hot tensile properties of GTA-welded tube joints of Super 304H austenitic stainless steel

Abstract: Background: Super 304H austenitic stainless steel tubes containing 2.3 to 3 (wt.%) of Cu are mainly used in superheaters and reheaters of ultra super critical boilers due their excellent corrosion and oxidation resistance. Cu addition causes precipitation strengthening effect by fine Cu-rich precipitates which evolve during creep conditions and results in increased creep strength. The microstructural evolution of stainless steels during welding significantly affects the material properties. Methods: In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…The results of the RT tensile test of the as-welded specimens are in accordance with results R p0.2 = 349.6 MPa ± 10.2 and R m = 614.6 ± 11.7 MPa presented in [2]. On the contrary, the rupture in [2] occurred in the base material, while in our case in the HAZ.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the RT tensile test of the as-welded specimens are in accordance with results R p0.2 = 349.6 MPa ± 10.2 and R m = 614.6 ± 11.7 MPa presented in [2]. On the contrary, the rupture in [2] occurred in the base material, while in our case in the HAZ.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the RT tensile test of the as-welded specimens are in accordance with results R p0.2 = 349.6 MPa ± 10.2 and R m = 614.6 ± 11.7 MPa presented in [2]. On the contrary, the rupture in [2] occurred in the base material, while in our case in the HAZ. The tensile test of the specimens with homogeneous welded joint regardless of solution annealing showed that after long-term aging (650 • C/7560 h) the yield strength decreased while the hardness value increased.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1573-6105.htm migration (Pandey et al, 2018a, b). The elemental segregation caused due to the variation also results in the induction of thermal stresses (Vinoth Kumar et al, 2015). Ferritic steels have lower thermal expansion coefficient than that of the austenitic steels which will increase the localized stress in the austenitic region (Laha et al, 2001).…”
mentioning
confidence: 99%